Edupreneurship Pengolahan Sampah sebagai Strategi Penanaman Ecological Citizenship pada Siswa - Heri Wibowo; Deni Zein Tarsidi; Joko Daryanto (STKIP Subang, 2026)
The continuously rising volume of waste and the low ecological citizenship awareness among the younger generation pose a crucial challenge to sustainable development. This research aims to comprehensively analyze the effectiveness and implementation of Waste Management Edupreneurship as an innovative strategy to instill Ecological Citizenship in Elementary School (SD) students. This study utilizes a systematic literature review methodology, examining various relevant academic journals published within the last decade. The literature analysis results indicate that Edupreneurship functions as a transformative mechanism that integrates entrepreneurial principles (innovation, creativity) with environmental education. The implementation of Edupreneurship at the elementary school level, particularly through activities that transform waste into products of economic value, is proven effective in facilitating the experiential learning that is vital for children in this age group. It was found that the implementation of waste management edupreneurship is an effective and validated pedagogical strategy for instilling the character of Ecological Citizenship in elementary students. The main success of this strategy lies in the utilization of the School Waste Bank (BASS), which serves as a platform for tangible action that simultaneously integrates the 3R principles (Reduce, Reuse, Recycle) with economic value. BASS is demonstrably a catalyst that transforms passive environmental awareness into proactive ecological responsibility. Through these activities, students are encouraged to form good citizenship behaviors rooted in sustained daily actions. Based on empirical and conceptual findings from various literature, this study formulates the T.E.P.A.K. Conceptual Model (Transformasi Edupreneurship Pengolahan Sampah Aksi Kewarganegaraan). This model is expected to be an optimal guide for achieving integrated cognitive, affective (character), and psychomotor learning outcomes within the context of environmental and citizenship education.